Building information modelling to support maintenance management of healthcare built assets. Issue 7 (7th May 2019) - Wanigarathna, Nadeeshani; Jones, Keith; Bell, Adrian; Kapogiannis, Georgios
Abstract : Purpose: This paper aims to investigate how digital capabilities associated with building information modelling (BIM) can integrate a wide range of information to improve built asset management (BAM) decision-making during the in-use phase of hospital buildings. Design/methodology/approach: A comprehensive document analysis and a participatory case study was undertaken with a regional NHS hospital to review the type of information that can be used to better inform BAM decision-making to develop a conceptual framework to improve information use during the health-care BAM process, test how the conceptual framework can be applied within a BAM division of a health-care organisation and develop a cloud-based BIM application. Findings: BIM has the potential to facilitate better informed BAM decision-making by integrating a wide range of information related to the physical condition of built assets, resources available for BAM and the built asset's contribution to health-care provision within an organisation. However, interdepartmental information sharing requires a significant level of time and cost investment and changes to information gathering and storing practices within the whole organisation. Originality/value: This research demonstrated that the implementation of BIM during the in-use phase of hospital buildings is different to that in the design and construction phases. At the in-use phase, BIM needs to integrate and communicate information within and between the estates, facilities division and other departments of the organisation. This poses a significant change management task for the organisation's information management systems. Thus, a strategically driven top-down organisational approach is needed to implement BIM for the in-use phase of hospital buildings.